Transformational Leadership and Social Impacts via Volunteer Social Business Model for SDG#3 and #17 - Yeung, Shirley Mo Ching (Journal of Ecohumanism, 2025)
This study explores the transformational leadership style of Dr. Yogananth Andiappan within the Andiappan Yoga Community (AYC), contextualized through the five steps of design thinking and SY Model (2016) endorsed by SGS ISO accreditation body 10 years ago. Drawing on Yeung’s SY Model framework, which emphasizes 7 principles of UNPRME and 17 UNSDGs, this research examines how Yogananth exemplifies transformational leadership by empower yoga volunteers with certification, fostering community empowerment via partnership with beneficiary number up to 92,000 in the annual report of 2023 with inclusivity and social innovations. Through qualitative analysis of analysing four years’ annual reports (2020 – 2023) with organizational practices and community engagement projects, the findings reveal that Yogananth Andiappan’s leadership promotes SDG#5 gender equity by encouraging active participation of women yoga trainers as volunteers, aligning with SDG#5 gender equality and SDG#8 decent jobs creation, facilitating the creation of meaningful employment opportunities, for example, project coordinators and yoga trainers/ MCs within the community. This leadership style underscores the importance of ecohumanistic values—empathy, sustainability, and social justice to drive positive social change. The study contributes to understanding how transformational leaders in nonprofit contexts with design thinking, SY Model (2016), UNPRME and UNSDGs for building sustainable wellness communities.